Bilateral fusion in primary mandibular teeth - Rachana V Prabhu; Laxmikanth Chatra; Prashant Shenai; Vishnudas Prabhu (Wolters Kluwer Medknow Publications, 2013)
Fusion has been described as a developmental anomaly characterized by the union of two adjacent teeth. Few cases of this rare anomaly in primary dentition have been reported in Indian population. A rare case of bilateral fusion between primary mandibular lateral incisors and canines is presented in this report.